|sin (x+ pi/3)| = cos (x- pi/3)

sin (x+ pi/3) = cos (x- pi/3) sin (x+ pi/3) =- cos (x- pi/3)

thats how far i understand (Worried)

cos( pi/2- (x+ pi/3)) = cos (x- pi/3) (Doh)

Printable View

- May 11th 2010, 09:12 AMRukiChareduce with module?
|sin (x+ pi/3)| = cos (x- pi/3)

sin (x+ pi/3) = cos (x- pi/3) sin (x+ pi/3) =- cos (x- pi/3)

thats how far i understand (Worried)

cos( pi/2- (x+ pi/3)) = cos (x- pi/3) (Doh) - May 11th 2010, 01:29 PMmohammadfawaz
I think your question is not very clear...can you please clarify what's the question?